Criterion Validity, and Interunit and Between-Day Reliability of the FLEX for Measuring Barbell Velocity During Commonly Used Resistance Training Exercises. Issue 6 (June 2020) - Weakley, Jonathon; Chalkley, Daniel; Johnston, Rich; García-Ramos, Amador; Townshend, Andrew; Dorrell, Harry; Pearson, Madison; Morrison, Matthew; Cole, Michael
Abstract : Abstract: Weakley, J, Chalkley, D, Johnston, R, García-Ramos, A, Townshend, A, Dorrell, H, Pearson, M, Morrison, M, and Cole, M. Criterion validity, and interunit and between-day reliability of the FLEX for measuring barbell velocity during commonly used resistance training exercises. J Strength Cond Res 34(6): 1519–1524, 2020—The aim of this study was to assess the criterion validity, interunit reliability (accounting for technological and biological variance), and between-day reliability of a novel optic laser device (FLEX) for quantifying mean concentric velocity. To assess the validity against a three-dimensional motion capture system and interunit reliability with both technological and biological variation, 18 men and women completed repetitions at 20, 40, 60, 80, 90, and 100% of one repetition maximum in the free-weight barbell back squat and bench press. To assess interunit (technological only) reliability, a purpose-built, calibrated rig completed a set protocol with 2 devices. To assess between-day reliability of the technology, the same protocol was repeated 21 days later. Standardized bias, typical error of the estimate (TEE; %), and Pearson's correlation coefficient ( r ) were used to assess validity, whereas typical error and coefficient of variation (CV%) were calculated for reliability. Overall, TEE (±90 CL) between the FLEX and criterion measure was 0.03 (±0.004) and 0.04 (±0.005) m·s −1 in the back squat and bench press, respectively. For measures of reliability, overall interunit technological variance (CV% [± 90% confidence interval]) was 3.96% (3.83–4.12) but increased to 9.82% (9.31–10.41) and 9.83% (9.17–10.61) in the back squat and bench press, respectively, when biological variance was introduced. Finally, the overall between-day reliability was 3.77% (3.63–3.91). These findings demonstrate that the FLEX provides valid and reliable mean concentric velocity outputs across a range of velocities. Thus, practitioners can confidently implement this device for the monitoring and prescription of resistance training loads.